Prenylated phenolics from Morus alba against MRSA infections as a strategy for wound healing - Škovranová, Gabriela; Čulenová, Marie; Treml, Jakub; Dzurická, Lucia; Marova, Ivana; Sychrová, Alice (Frontiers in Pharmacology, 2022)
Antimicrobial resistance is a public health threat and the increasing number of multidrug-resistant bacteria is a major concern worldwide. Common antibiotics are becoming ineffective for skin infections and wounds, making the search for new therapeutic options increasingly urgent. The present study aimed to investigate the antibacterial potential of prenylated phenolics in wound healing. Phenolic compounds isolated from the root bark of Morus alba L. were investigated for their antistaphylococcal potential both alone and in combination with commonly used antibiotics. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined by microdilution and agar method. Synergy was investigated using the checkerboard titration technique. Membrane-disrupting activity and efflux pump inhibition were evaluated to describe the potentiating effect. Prenylated phenolics inhibited bacterial growth at lower concentrations than commonly used antibiotics. The combination of active phenolics with kanamycin, oxacillin, and ciprofloxacin resulted in a decrease in the MIC of the antimicrobial agent. Kuwanon C, E, T, morusin, and albafuran C showed synergy with oxacillin and/or kanamycin. Prenylated phenolics disrupted membrane permeability statistically significantly, and membrane disruption contributes to the complex antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). In addition, kuwanon C could be considered an efflux pump inhibitor. Despite the antibacterial effect on MRSA and the multiple biological activities, the prenylated phenolics at microbially significant concentrations have a minor effect on human keratinocyte (HaCaT) viability. In conclusion, prenylated phenolics in combination with commonly used antibiotics are promising candidates for the treatment of MRSA infections and wound healing, although further studies are needed.